2002
DOI: 10.1038/417292a
|View full text |Cite
|
Sign up to set email alerts
|

A common mechanism of action for three mood-stabilizing drugs

Abstract: Lithium, carbamazepine and valproic acid are effective mood-stabilizing treatments for bipolar affective disorder. The molecular mechanisms underlying the actions of these drugs and the illness itself are unknown. Berridge and colleagues suggested that inositol depletion may be the way that lithium works in bipolar affective disorder, but others have suggested that glycogen synthase kinase (GSK3) may be the relevant target. The action of valproic acid has been linked to both inositol depletion and to inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
493
3
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(528 citation statements)
references
References 21 publications
23
493
3
9
Order By: Relevance
“…Harwood and co-workers have extended this strategy to include carbamazepine and have shown in cell cultures that all three mood stabilizers inhibit the collapse of growth cones and increase growth cone area. This likely happens independently of GSK-3b or histone deacylase inhibition but is possibly dependent on inositol depletion (Williams et al, 2002). We have extended the above cellular and molecular studies by testing valproate effects on circadian rhythms and shown that, similar to lithium, valproate lengthens the circadian period and the rate of arrhythmicity albeit with smaller effect size.…”
Section: Discussionmentioning
confidence: 83%
“…Harwood and co-workers have extended this strategy to include carbamazepine and have shown in cell cultures that all three mood stabilizers inhibit the collapse of growth cones and increase growth cone area. This likely happens independently of GSK-3b or histone deacylase inhibition but is possibly dependent on inositol depletion (Williams et al, 2002). We have extended the above cellular and molecular studies by testing valproate effects on circadian rhythms and shown that, similar to lithium, valproate lengthens the circadian period and the rate of arrhythmicity albeit with smaller effect size.…”
Section: Discussionmentioning
confidence: 83%
“…Among those, inhibition of the inositol monophosphatase was suggested to be a common mechanism of action of three mood stabilizers (Williams et al, 2002). Inhibition of the inositol monophosphatase has been shown to increase inositol monophosphates and to decrease myoinositol concentrations in rat brain (O'Donnell et al, 2000), although in humans, this effect has not consistently been observed (Silverstone et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Par ailleurs, les inhibiteurs sélectifs de la POP exercent des actions pro-mnésiques et anti-amné-siques chez les primates et chez l'homme [11,12] Li + POP troubles de la mémoire [13]. [6]. Ces données constituent la pierre angulaire de leur étude puisqu'elles démontrent qu'en dépit de leurs multiples actions intracellulaires, les trois thymorégulateurs exercent un effet commun sur la croissance neuritique.…”
unclassified
“…Ces données constituent la pierre angulaire de leur étude puisqu'elles démontrent qu'en dépit de leurs multiples actions intracellulaires, les trois thymorégulateurs exercent un effet commun sur la croissance neuritique. L'ajout d'inositol au milieu de culture abolit les effets du lithium, de l'acide valproïque et de la carbamazépine sur le nombre et la taille des cônes de croissance, révélant pour la première fois que le cycle des phospho-inositides est la cible commune des thymorégulateurs chez les mammifères [6]. Ces travaux soulignent donc toute la pertinence des stratégies thérapeutiques visant à moduler le métabolisme des phosphatidyl inositols pour le traitement des psychoses maniaco-dépressives.…”
unclassified
See 1 more Smart Citation